Accelerated Trajectories of Walking Capacity Across the Adult Life Span in Persons With Multiple Sclerosis: An Underrecognized Challenge. (April 2020) - Hvid, Lars G.; Feys, Peter; Baert, Ilse; Kalron, Alon; Dalgas, Ulrik
Background . In the general population, trajectories of walking capacity is accelerated and nonlinear with advanced age. Whether this is more pronounced in persons with multiple sclerosis (pwMS), along with the prevalence of dismobility (ie, slow gait speed), are currently unknown. Our objective was to investigate trajectories of walking capacity and prevalence of dismobility across the adult life span in pwMS versus healthy controls (HC). Methods . Data on maximal timed 25-foot walk test (T25FWT), 2-minute walk test (2MWT), and 6-minute walk test (6MWT) along with prevalence of dismobility were assembled from 2 RIMS multicenter studies (n = 502 pwMS; age range 21-77 years, 6 age groups: 20-29, 30-39, 40-49, 50-59, 60-69, and 70-79 years). HC data were extracted from studies containing normative reference values (n = 1070-3780 HC). Results . Age trajectories of walking capacity was nonlinear and accelerated in pwMS versus HC. While measures of walking capacity in pwMS were suppressed already early in life, the gap between pwMS and HC significantly widened across the 6 age groups (pwMS performed 64%, 70%, 57%, 59%, 51%, and 37% of HC, respectively). This coincided with high prevalences of dismobility in pwMS across the 6 age groups when using usual gait speed cut-point values <1.0 m/s (corresponding to 33%, 32%, 51%, 59%, 75%, and 100%) and <0.6 m/s (corresponding to 19%, 12%, 26%, 23%, 33%, and 43%), markedly exceeding that observed in HC. Conclusion . The present data on walking capacity provide evidence for an accelerated deterioration in pwMS with advanced age, coinciding with high prevalences of dismobility (ie, slow gait speed).